THE EFFECT OF DIORAMA MEDIA ON THE LEARNING OUTCOMES OF PANCASILA EDUCATION FOR 3RD GRADE STUDENTS AT SD MUHAMMADIYAH 1 KEDUNGGALAR NGAWI - Annisa Dhiya Azzahra; Dita Primashanti Koesmadi; Uci Ulfa Nur’afifah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Education plays a central role in the development of students' character and knowledge. One of the subjects that significantly influences the shaping of national character is Pancasila Education. In the implementation of Pancasila education in elementary schools, engaging learning media is essential. The use of instructional media in the teaching and learning process contributes positively to the overall psychological development of children. Diorama media is a three dimensional miniature learning media designed to demonstrate and depict real forms visualized in the classroom. Diorama media can help explain learning processes that were previously abstract into more concrete forms. The design of this research is a One-Group Pretest-Posttest Design. The sample for this reseach is also the 20 third-grade students at SD Muhammadiyah 1 Kedunggalar. Based on the research results and discussion, the paired sample t-test showed a Sig. (2-tailed) value of 0.000 < 0.05. Therefore, Ho is rejected and Ha is accepted. There is a significant difference between the students’ pretest and posttest scores. The pretest had an average (mean) score of 60.50, while the posttest average (mean) score was 86.50. The increase in the average scores between the two tests indicates an improvement in student performance. Thus, it can be concluded that the use of diorama media positively affects the learning outcomes of Pancasila Education for first-grade students at SD Muhammadiyah 1 Kedunggalar.